WOMEN`S FREEDOM IN TONI MORRISON`S SULA - Bertova Simanihuruk; Naomi Fatricia Surbakti (Muse: Jurnal of Art, 2025)
This study examines the concept of women’s freedom in Toni Morrison's Sula, an important and relevant topic, particularly within the context of a patriarchal culture that continues to shape the lives of many women. The research focuses on the family and societal factors influencing women’s experiences. Employing a narrative qualitative methodology, the primary data is derived from Sula by Toni Morrison, supplemented by relevant literature from library research. The study applies feminist theory as proposed by Soenarjati Djajanegara, emphasizing the impact of family expectations and social conventions on individuals and their roles within society. The findings reveal that two key components shape women’s lives: family expectations and social conventions. Family expectations are often portrayed as burdens that restrict women’s freedom, while social conventions are the traditional norms, rules, and gender roles that govern how women are expected to behave, interact, and live. The analysis concludes that women need freedom to empower themselves and realize their potential. However, this freedom must not lead to self-destruction or harm to others, as such outcomes can result in women’s downfall.